2020
DOI: 10.24059/olj.v24i4.2332
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous Online Discussions During Case-Based Learning: A Problem-Solving Process

Abstract: Asynchronous discussions are typically considered an essential aspect of online case-based learning. While instructors implement discussions to support a variety of instructional purposes during case-based learning (e.g., facilitate students’ sense making, prompt the consideration of diverse perspectives, debate complex topics), whether students receive the expected benefits is unclear, and little research has considered how students intentionally participate in discussions to support their learning during cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…Some of the advantages of this method are as follows: (1) Students develop connections between their knowledge and existing problems. (2) The provision of the opportunity to consider similar real-world problems (Koehler, Fiock, Janakiraman, Cheng, & Wang, 2020). (3) Development of critical thinking skills, teamwork and cultural awareness (Yadav, Bozic, Gretter, & Nauman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the advantages of this method are as follows: (1) Students develop connections between their knowledge and existing problems. (2) The provision of the opportunity to consider similar real-world problems (Koehler, Fiock, Janakiraman, Cheng, & Wang, 2020). (3) Development of critical thinking skills, teamwork and cultural awareness (Yadav, Bozic, Gretter, & Nauman, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…More study and theorization on this concept are certainly needed to understand how and why the higher degree of live discussion was observed to have a lesser effect than the mid-range live-discussion condition and the asynchronous-only condition. In terms of social presence, live interactions are thought of to be a "richer" learning experience but may not always be necessary to indicate the presence of other individuals and groups (Chen, Park, & Hand, 2016;Garrison, 2016;Koehler et al, 2020). In today's digital ecosystem, a high degree of live discussions may serve to be distracting for some individuals or demand a high level of cognitive load, which may actually counter the benefits of the learning activity.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunities for social interaction can activate the interpersonal and transactive processes that are essential for learning and meaning-making processes, such as discussing and determining the meaning of phenomena and concepts, debating concepts, and encountering other points of view to refine one's own understanding (Kozan & Richardson, 2014). Toward this focus on social presence, it has been regularly observed that the expectation of the degree and timing of which participants will interact will often influence variations in the type of behaviors that are exhibited in learning environments (Chen, Park, & Hand, 2016;Coffin, Hewings, & North, 2012;Koehler et al, 2020).…”
Section: Considering Simultaneity Of Social Interaction and Social Pr...mentioning
confidence: 99%
“…From these studies, we learn that learners who participate in online discussions perceive that it contributes to their learning (55). More specifically, although some learners value teamwork in the resolution of online cases and others do not, all look to the instructor for direction, instruction, and feedback (56). The role of the instructor for facilitating cases in the online environment cannot be understated; in fact, it is a finding that is consistently found across all studies.…”
Section: Discussionmentioning
confidence: 99%